Pelvic floor muscle exercises alleviate symptoms and improve mental health and rectal function in patients with low anterior resection syndrome - Yuanyuan, Wu; Shiyin, He; Lei, He; Ding, Ding (Frontiers in Oncology, 2023)
Background Pelvic floor rehabilitation has been reported to be effective in improving fecal incontinence. The aim of this study was to prospectively evaluate the effectiveness of combined pelvic floor muscle exercises (PFMEs) and loperamide treatment on rectal function and mental health for low anterior resection syndrome (LARS) patients after sphincter-saving operation (SSO) for rectal cancer. Methods A total of 60 inpatients diagnosed with LARS were enrolled and randomly assigned to one of two groups: patients in Group A (n = 30) were treated with a PFME intervention and those in Group B (n = 30) with a control intervention for 4 weeks. High-resolution anorectal manometry (HRAM) was performed for all LARS patients. Demographic information was collected for all patients, and they subsequently also completed several questionnaires, including the Hospital Anxiety and Depression Scale (HADS), a measure of Wexner score, a measure of stool frequency per day, and the Bristol Stool Form Scale (BSFS). Results No significant differences between the groups were observed in baseline data. With regard to rectal function, we found significant improvements at week 4 in maximal resting pressure (MRP) (39.93 ± 5.02 vs. 28.70 ± 5.40 mmH2O, p < 0.001) and maximal squeeze pressure (MSP) (132.43 ± 8.16 mmH2O vs. 113.33 ± 9.87 mmH2O, p < 0.001) among Group A patients compared to Group B patients. Additionally, Wexner scores were significantly lower in Group A than in Group B at week 4 (8.10 ± 1.24 vs. 9.87 ± 1.29 ml, p = 0.018), as were stool frequency (6.47 ± 0.90 vs. 7.83 ± 0.93, p < 0.001) and BSFS scores (5.17 ± 0.65 vs. 6.10 ± 0.80, p = 0.020). Notably, HADS scores were also significantly lower in Group A than in Group B at week 4 (8.25 ± 2.36 vs. 10.48 ± 3.01, p < 0.001). Additionally, both anxiety scores (4.16 ± 1.38 vs. 5.33 ± 1.69, p < 0.001) and depression scores (4.09 ± 1.56 vs. 5.15 ± 1.89, p < 0.001) were significantly lower in Group A than in Group B at week 4. Conclusion Pelvic floor muscle exercises are an effective treatment that can alleviate symptoms and improve rectal function and mental health in patients with low anterior resection syndrome.